Race and multiculturalism in Malaysia and Singapore [ - Goh Pei Siong, Daniel (Routledge Malaysian studies series, 2009)
This book explores race and multiculturalism in Malaysia and Singapore from a range of different disciplinary perspectives showing: how race and multiculturalism are represented, how multiculturalism works in practice, and how attitudes towards race and multiculturalism - and multicultural practices - have developed over time.